2021
DOI: 10.1101/2021.11.30.470689
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthetic evolution of herbicide resistance using a T7 RNAP-based random DNA base editor

Abstract: Synthetic directed evolution via localized sequence diversification and the simultaneous application of selection pressure is a promising method for producing new, beneficial alleles that affect traits of interest in diverse species; however, this technique has rarely been applied in plants. Developing systems to induce localized sequence diversification at high efficiency will expand our ability to evolve traits of interest that improve global food security. In this study, we designed, built, and tested a chi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…[147,148] In addition, the application of T7 expression system in nanotechnology and nanomaterial indicates a promising potential in gene therapy. The combination of T7 system with deaminase, [149][150][151] CRISPR/Cas9 expression system, and optical genetic provides effective tools for genome editing in eukaryote. [152,153] Furthermore, in vitro T7 expression system has been applied extensively to detect various biomolecules, especially in clinical diagnosis, which facilitates the development of cell-free synthetic biology in eukaryote.…”
Section: Discussionmentioning
confidence: 99%
“…[147,148] In addition, the application of T7 expression system in nanotechnology and nanomaterial indicates a promising potential in gene therapy. The combination of T7 system with deaminase, [149][150][151] CRISPR/Cas9 expression system, and optical genetic provides effective tools for genome editing in eukaryote. [152,153] Furthermore, in vitro T7 expression system has been applied extensively to detect various biomolecules, especially in clinical diagnosis, which facilitates the development of cell-free synthetic biology in eukaryote.…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It The deaminase-T7RNAP system was first reported in bacteria (MutaT7; (Moore et al, 2018)) and further extended to mammalian cells (TRACE; (Chen et al, 2020)), yeast (TRIDENT; (Cravens et al, 2021)), and plants (Butt et al, 2021). We previously demonstrated that the mutation rate of MutaT7 could be enhanced 7-to 20-fold with a more efficient cytidine deaminase, Petromyzon marinus cytidine deaminase (PmCDA1) (Park & Kim, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that most directed evolution experiments focus on a single protein, the ideal target range is a single gene of interest. Gene-specific targeting was achieved through homologous platforms that use chimeric mutator proteins, generated by fusing a nucleobase deaminase to an orthogonal T7 RNA polymerase (T7RNAP) (Alvarez et al , 2020; Butt et al , 2021; Chen et al , 2020; Cravens et al , 2021; Moore et al , 2018; Park & Kim, 2021).…”
Section: Introductionmentioning
confidence: 99%